2016
DOI: 10.3390/ani6020009
|View full text |Cite
|
Sign up to set email alerts
|

Heat Tolerance in Curraleiro Pe-Duro, Pantaneiro and Nelore Cattle Using Thermographic Images

Abstract: The objective of this study was to compare physiological and thermographic responses to heat stress in three breeds of cattle. Fifteen animals of each of the Nelore, Pantaneiro and Curraleiro Pe-Duro breeds, of approximately two years of age, were evaluated. Heart and respiratory rates, rectal and surface temperature of animals as well as soil temperature were recorded at 8:30 and 15:30 on six days. Variance, correlation, principal factors and canonical analyses were carried out. There were significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…In this regard, Brazilian locally adapted cattle breeds represent an important genetic resource for the understanding of the role of natural selection in diverse environments, providing new insights into the genetic mechanisms inherent to adaptation and survivorship [6]. Although their productivity is much lower compared to highly-specialized breeds under intensive production systems [7,8], great efforts have been made to improve our knowledge of locally adapted breeds [5,9,10] and their use in crossbred schemes.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Brazilian locally adapted cattle breeds represent an important genetic resource for the understanding of the role of natural selection in diverse environments, providing new insights into the genetic mechanisms inherent to adaptation and survivorship [6]. Although their productivity is much lower compared to highly-specialized breeds under intensive production systems [7,8], great efforts have been made to improve our knowledge of locally adapted breeds [5,9,10] and their use in crossbred schemes.…”
Section: Introductionmentioning
confidence: 99%
“…The arrival of a technological innovation generates a large impact on elements of an industry (HANNACHI; TICHIT, 2016). The use of thermographic images have long been used in production systems as a technological tool in the diagnosis of diseases (MCMANUS et al, 2016), as in studies of parasitic tick infestation in cattle (CORTIVO et al, 2016), in bioclimatology (CARDOSO et al, 2016; GEORGE, 2014 ) on animal welfare (STEWART et al, 2005) and animal reproduction (SCOLARI et al, 2009;RAMIRES NETO et al, 2011;SIMÕES et al, 2014;CRUZ JÚNIOR et al, 2015;ALVES et al, 2016). In present study, the identification of estrous in goats showed that the infrared thermography can be a promising technique, and to a highly repeatable method for evaluation of skin temperature in goats.…”
Section: Discussionmentioning
confidence: 99%
“…Regression analysis using infrared thermographic temperatures from different points of animal's body to predict the average daily gain (ADG) in 2 genetic groups (GG; Nelore and F1-Nelore × Angus) The analysis was carried out using all dataset (both) and separated by season (dry and rainy) and by genetic group (Nelore and F1-crossbred Angus × Nelore). for heat tolerance evaluation (Cardoso et al, 2015(Cardoso et al, , 2016. Nelore animals exposed to air temperatures higher than 30 °C exchanged heat mainly by cutaneous evaporation (Costa et al, 2018) for which the dewlap region plays an important role.…”
Section: Discussionmentioning
confidence: 99%
“…1 8 32 0 55 1 100 1 8 32 58 H The QuickReport software was used to collect data from thermographic images (Cardoso et al, 2015(Cardoso et al, , 2016. The software used the input of the ambient temperature and humidity of the exact moment of the photo as adjust factors for the output.…”
Section: Methodsmentioning
confidence: 99%